Gaya Hidup Digital, Literasi Keuangan, dan Persepsi Risiko: Faktor Penentu dalam Penggunaan Qris Sebagai Transaksi Digital - Hidayanti, Nur Fitri; Ariani, Zaenafi (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
Digital transformation in the payment system has encouraged the adoption of Quick Response Code Indonesian Standard (QRIS) based transaction methods. This study aims to identify and analyze the main factors that influence the use of QRIS as a digital payment method with a Systematic Literature Review (SLR) approach. Literature sources were obtained from Scopus, DOAJ, and Google Scholar indexed databases with publication coverage in the last 10 years. The results show that digital lifestyle is the main driving factor in QRIS adoption, especially among Generation Z who have a high level of technological skills and a tendency to use non-cash payments. In addition, financial literacy plays an important role in increasing users' confidence in utilizing QRIS, where individuals with better financial understanding tend to be more open to digital payment systems. However, risk perception remains an obstacle to QRIS adoption, specifically related to data security and potential cybercrime. The study also found that the COVID-19 pandemic has accelerated the transition to digital transactions, making QRIS a safer and more efficient payment alternative. Nonetheless, challenges in improving financial literacy, especially among MSMEs and older age groups, as well as the need for clearer regulations in ensuring system security, are still aspects that need attention. Therefore, further research is needed to explore strategies to increase QRIS adoption through educational approaches, regulatory policies, and strengthening digital infrastructure to expand financial inclusion in Indonesia.